Ansiedade, estresse e depressão de familiares de pacientes com insuficiência cardíaca em tratamento ambulatorial - Lacerda, Marianna Sobral [UNIFESP] (2016)
To analyze the level of anxiety and stress as well as the symptoms of depression in relatives accompanying patients with Heart Failure under outpatient treatment; to describe the sociodemographic and clinical characteristics of relatives accompanying patients with HF under outpatient treatment, and also those related to the way of life and burden; to verify whether there is correlation among the scores of scales of anxiety, depression and stress and verify whether there are differences in the scores of scales of anxiety, depression and stress according to sociodemographic and clinical characteristics, as well as those related to the way of life and burden of relatives and the degree of independence with regard to activities of daily living of patients. Method: This is a cross-sectional and descriptive study, which was performed between April 2014 and February 2015 in the Cardiomyopathy Outpatient Clinic of the São Paulo Hospital. The sample was composed by 100 relatives of patients with Heart Failure. The anxiety, the depression and the stress were evaluated by means of Beck Anxiety Inventory, Beck Depression Inventory and Perceived Stress Scale - 10, respectively. The other variables were obtained by means of an instrument containing the sociodemographic and clinical variables, the self-rated health, the Index of Independence in Activities of Daily Living and Caregiver Burden Scale. Results: The average age of surveyed subjects was 45.43±13.53 years, most were female (81%), white (63%) and married (61%). The score of depression showed an average of 8.24±7.14, the anxiety was 7.95±7.61 and the stress scale was 17.43±7.15, thereby demonstrating the lack of these symptoms in most relatives of patients with HF. As for the degree of independence, 82% of patients were independent for all activities of daily living, and there was no burden of caregiver (17,9±14,21). The correlation coefficient among the scales was 0.53 between depression and anxiety, and between depression and stress, and 0.66 between anxiety and stress. Female gender (p=0.002; p=0.031), smoking (p=0.05; p=0.011), sedentariness (p=0.023; p=0.001) and regular/bad selfrated health (p=0.012; p=0.013) showed a relationship with anxiety and stress. The family income less than 5 minimum wages (p=0.012) and the regular/bad health selfassessment (p=0.001) were associated with depression. Conclusion: Relatives did not show high levels of stress, anxiety and depression. The scales showed correlation with each other, but the scales of stress and anxiety showed greater correlation strength. Self-rated health, physical activity, smoking and gender were the factors that showed a relationship with stress and anxiety, and family income and self-rated health were factors related to symptoms of depression.